A Mobile-Based Counselling Application to Evaluate SMK Putrajaya Presint 9(2) Students - Ghazali, Nur Azura; Aman, Hannani (Applied Information Technology And Computer Science, 2022)
In educational pedagogy, counselling is very important for students. They remain in contact with the counsellor to figure out their personality traits for future taking. Nowadays, schools use papers in order to take student information and for counsellor to evaluate traits, monitor progress and personality each student. This engagement students and counsellor only happen during students in school session. Current system maintains every student data in hard copies which takes possibility of data duplication and chances of human mistakes is high and also may cause easy security breach.  Therefore, to overcome data duplication, human error handling and secure every data, Sekolah Menengah Kebangsaan Putrajaya Presint 9(2) (SMKPP9(2)) Counselling Application is developed. This project intention is to make a computerized based system also via mobile application and support counsellor in managing self-esteem questionnaire in effective way. Object-oriented methodology is used to assist development of the application. Java language is used to develop this system and Firebase as a database software. This system contains nine modules which are login, add student account, view student list, self-esteem test, view result, book appointment, manage appointment and generate report. The testing result shows 28 over 30 test cases pass the testing.  In conclusion, this system is expected to be easy for counselor to use an application where they can manage data and store student counselling process in automated computerized system.